Effectiveness of Monetary Policy in Morocco: Stability and Implications - Erraiteb, Meryem (International Journal of Economics, Business, and Entrepreneurship, 2020)
The purpose of this study is evaluating the effectiveness of monetary policy in Morocco. The results suggest that the monetary authorities must get out of the narrowness of logic monetarist by adopting a new approach which explicitly privileges the targeting of inflation as the ultimate goal, while referring to a multitude of indicators likely to guide the Central Bank in the conduct of its monetary policy as the exchange rate and interest rate next to the M3 aggregate growth rule. Thus, monetary authorities should out of the narrow sense monetarist by adopting a new approach that focuses explicitly targeting inflation as the ultimate goal, while referring to a multitude of indicators to guide the central bank in the conduct of monetary policy as exchange rate and Interest rate ET and this, alongside the growth rule M3.